Transformasi Digital Mengubah Lanskap Bisnis UMKM di Era Teknologi - Annisa Novianti; Munawaroh Munawaroh (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Advances in information technology have brought major changes in various sectors, including business and the economy. Digital technology, such as the internet and platform-based applications, provides opportunities for MSMEs to expand marketing reach, increase operational efficiency and increase customer satisfaction. Digital transformation is a necessity for MSMEs to compete and adapt in the digital economy era, where information technology allows them to reach wider markets and manage business operations more efficiently. Research shows that MSMEs that utilize digital platforms tend to be more resilient in facing economic challenges, including crises. Digital transformation does not only involve technology adoption, but also changes in the culture and mindset of the organization as a whole. The development of "Digital Entrepreneurship" is an important strategy to strengthen the competitiveness of MSMEs through innovation in marketing, financial management, collaboration and product design. However, MSMEs face obstacles such as limited human resources and access to capital for technology investment. Digitalization provides significant opportunities to increase the productivity and competitiveness of MSMEs in the global market, especially in the era of Industrial Revolution 4.0. However, obstacles such as the digital divide and lack of technological knowledge remain challenges. Therefore, government support and collaboration from various parties is needed to accelerate sustainable and inclusive digital transformation, which ultimately contributes to strengthening Indonesia's digital economy.